I-RANT: Training session on a novel, scripted, bystander microaggression intervention tool for medical students - Emily Grass; Caroline Astemborski; James M Lewis (BMC Medical Education)
Abstract Background Microaggressions, subtle and often unintentional acts of hostility, have been recognized as a significant issue in healthcare, adversely affecting learners’ emotional and physical well-being. Current strategies for addressing microaggressions are broad frameworks without empirical substantiation that leave learners without a clear direction for intervention. This study introduces a novel scripted, succinct, bystander intervention tool to combat microaggressions. The intervention tool developed by the research team, named I-RANT, follows the script of introduction, role naming, affirming the target, negating the microaggression, and transitioning within patient encounters. The study goal was to assess the ability of a training session to impact learners’ recognition of microaggressions, confidence in intervening, and competency in applying the I-RANT tool. Methods A pre-experimental study was conducted with 97 second-year medical students at a large academic center in the Southeast United States. The I-RANT tool was taught through a 90-minute training session. The session included an introduction lecture, small group discussions, and role-play scenarios. Pre- and post-intervention surveys assessed microaggression recognition via a multiple-choice questionnaire (MCQ) and self-reported confidence in intervening on a Likert scale. Differences were compared via paired T-test. Role-play scenarios were observed by trained faculty and graded for competence using a rubric. Results Participants showed significant improvement in microaggression identification with increase in MCQ score from 4.17 (SD 0.75) pre-intervention to 4.74 (SD 0.42) post-intervention (p < .001) and increased self-reported confidence from 3.2 (SD 1.0) to 4.2 (SD 0.63) (p < .001). Trained faculty evaluated a random sampling of students’ role-play scenarios (n = 30) revealing that 97% of sampled students demonstrated competence in utilizing the I-RANT tool. Discussion The I-RANT training session empowered learners to address microaggressions. Learners demonstrated a statistically significant improvement in recognition of microaggressions and confidence in intervening. The majority of learners demonstrated competency in utilizing the I-RANT tool by the end of the training session. Conclusions This study supports the effectiveness of our training session in enhancing medical students’ ability to recognize and address microaggressions. I-RANT empowers learners with a tool to intervene against microaggressions within patient encounters.